2017
DOI: 10.1038/s41598-017-05808-w
|View full text |Cite
|
Sign up to set email alerts
|

RLR-mediated antiviral innate immunity requires oxidative phosphorylation activity

Abstract: Mitochondria act as a platform for antiviral innate immunity, and the immune system depends on activation of the retinoic acid-inducible gene I (RIG-I)-like receptors (RLR) signaling pathway via an adaptor molecule, mitochondrial antiviral signaling. We report that RLR-mediated antiviral innate immunity requires oxidative phosphorylation (OXPHOS) activity, a prominent physiologic function of mitochondria. Cells lacking mitochondrial DNA or mutant cells with respiratory defects exhibited severely impaired virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 42 publications
3
44
0
Order By: Relevance
“…Mitochondria are known to play an important role in innate immune responses against RNA viruses [20][21][22][23] . Recognition of cytosolic viral RNA by retinoic acid-inducible gene I (RIG-I)-like receptors (RLR) and their downstream processes have been shown to require the participation of mitochondrial antiviral signaling (MAVS), a mitochondrial outer membrane adaptor protein 20,24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are known to play an important role in innate immune responses against RNA viruses [20][21][22][23] . Recognition of cytosolic viral RNA by retinoic acid-inducible gene I (RIG-I)-like receptors (RLR) and their downstream processes have been shown to require the participation of mitochondrial antiviral signaling (MAVS), a mitochondrial outer membrane adaptor protein 20,24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper showed that Drp1-dependent mitochondrial dynamic was coupled with oxidative respiration: tubular mitochondria was accompanied with increased oxidative respiration, while fragmented mitochondria achieved the opposite [37]. The oxidative phosphorylation activity was supposed to be required in the RLR innate immune signaling, as SeV-induced IFN production was impaired in cells with oxidative phosphorylation defect, but was restored when the oxidative phosphorylation was recovered [38]. In our study, increased tubular mitochondrial and impaired SeV-induced IFN production was observed in PLA1A knockdown cells.…”
Section: Discussionmentioning
confidence: 99%
“…ROS can induce aggregation of MAVS on mitochondrial outer membrane to initiate IFN response. Cells with reduced ETC activity are impaired with production of IFNs and proinflammatory cytokines during viral infection . In contrast, increased ROS production counteracts HCV replication .…”
Section: The Mutual Interactions Between Hepatitis Viruses and Mitochmentioning
confidence: 99%